Evolution of the Concept of Evolution - Mikhailovsky George (Journal of Evolutionary Science, 2018)
A historical and conceptual review traces how evolutionary theory has expanded from classical selection to modern syntheses incorporating development, epigenetics, and systems thinking. Implications for research and science communication are discussed.